(untitled) (diségno, 2021)
The III Convegno Internazionale e Interdisciplinare su Immagini e Immaginazione/3rd International and Interdisciplinary Conference on Image and Imagination, IMG2021 Image Learning, was held in the presence, on 25 and 26 November at the Politecnico of Milan. [read more]